Polypharmacy and mobility outcomes. (December 2020) - Ali, Muhammad Usman; Sherifali, Diana; Fitzpatrick-Lewis, Donna; Kenny, Meghan; Liu, April; Lamarche, Larkin; Mangin, Derelie; Raina, Parminder
Highlights: This review identified 9 primary studies that investigate the effects of polypharmacy interventions on mobility outcomes. The evidence showed polypharmacy interventions have positive effects on mobility outcomes demonstrated by falls incidence reductions. There was a signal of potential effect in observational studies on physical function tests. There is limited evidence for effects on activities of daily living or falls related mortality. Abstract: Polypharmacy is known to be associated with negative consequences of mobility related conditions such as falls, functional decline and disability. This systematic review highlights the effectiveness of deprescribing interventions on mobility related conditions in older adults in the community dwelling reported taking five or more medications daily.